1999
DOI: 10.1029/1998jd100087
|View full text |Cite
|
Sign up to set email alerts
|

Design and initial characterization of an inlet for gas‐phase NOy measurements from aircraft

Abstract: Abstract. An understanding of gas-phase HNO3 transmission through an inlet is necessary to evaluate the quality of NOy measurements from an aircraft platform. A simple, inexpensive, low-volume Teflon inlet is described and its suitability as an aircraft inlet for gas-phase NOy is assessed. Aerosol transmission is not characterized, but inlet design and orientation probably discriminates against the majority of aerosol by mass. Laboratory data, in-flight HNO3 standard addition calibrations, and ambient NOy meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 19 publications
0
112
0
1
Order By: Relevance
“…These data and issues of CO calibration and standardisation are discussed by Bauguitte et al (2008) Nitric acid is notoriously difficult to collect and measure because of its tendency to stick to any available surface (see e.g. Ryerson et al, 1999). Apart from the more expensive routes (such as Chemical Ionisation Mass Spectrometry), three main methods have been used to sample HNO 3 in the past: nylon filters, annular denuders, and mist chambers.…”
Section: Carbon Monoxidementioning
confidence: 99%
“…These data and issues of CO calibration and standardisation are discussed by Bauguitte et al (2008) Nitric acid is notoriously difficult to collect and measure because of its tendency to stick to any available surface (see e.g. Ryerson et al, 1999). Apart from the more expensive routes (such as Chemical Ionisation Mass Spectrometry), three main methods have been used to sample HNO 3 in the past: nylon filters, annular denuders, and mist chambers.…”
Section: Carbon Monoxidementioning
confidence: 99%
“…By contrast to HNO 3 our lab studies have shown that SO 2 is not affected by adsorption on and/or desorption from sampling-line surfaces (Teflon and stainless steel). Unfortunately, in contrast to inlet systems for aircraftborne measurements of HNO 3 (Kondo et al, 1996;Ryerson et al, 1999), attention has only recently been directed to the development of a proper sampling system for groundbased and long-term continuous measurements of HNO 3 in the boundary layer where the air is usually characterized by high relative humidities and heavy aerosol loading Furutani et al, 2002;Mauldin et al, 1998;Neuman et al, 1999).…”
Section: Inlet For Sampling Ambient Airmentioning
confidence: 99%
“…Total weight was approximately 270 kg and power consumption was about 2 kW. The inlet was machined from PFA Teflon following the design of Ryerson, et al (1999). Pinholes just prior to each LIF cell gave pressures of 1-5 hPa over the 0-8 km altitude range, with a flow rate of 2 liters per minute per channel at sea level.…”
Section: Airborne Measurementsmentioning
confidence: 99%